Mandates and democracy : neoliberalism by surprise in Latin America - Stokes, Susan Carol (Cambridge studies in comparative politics., 2001)
"Sometimes politicians run for office promising one set of policies and then, if they win, they switch to very different ones. Latin American presidents in recent years have frequently run promising to avoid pro-market reforms and harsh economic adjustment, then win and transform immediately into enthusiastic market reformers. Does it matter when politicians ignore the promises they made and the preferences of their constituents? If politicians want to be reelected or see their party reelected at the end of their term, why would they impose unpopular policies? Susan Stokes explores questions of mandates, promises, and democratic theory in light of the Latin American experience. She develops a model of policy switches and tests it with statistical and qualitative data from Latin American elections over the last two decades. She concludes that politicians may change course because they believe that unpopular policies are best for constituents and hence also will best serve their own political ambitions. Nevertheless, even though good representatives will sometimes switch policies, abrupt changes of course tend to erode the quality of democracy."--Jacket